Anthocyanin Genes Involved in the Flower Coloration Mechanisms of Cymbidium kanran - Zhou, Zhuang; Ying, Zhen; Wu, Zhigang; Yang, Yanping; Fu, Shuangbin; Xu, Wan; Yao, Lijuan; Zeng, Aiping; Huang, Jian; Lan, Siren; Wang, Xiaole; Liu, Zhongjian (Frontiers in Plant Science, 2021)
The Orchidaceae (orchids) is one of the largest plant families and is renowned for its spectacular flowers and ecological adaptations. Various polymorphisms of orchid flower color can attract pollinators and be recognized as valuable horticultural ornamentals. As one of the longest historic cultured orchids, Cymbidium kanran has been domesticated for more than 2,500 years and is an ideal species to study coloration mechanisms because of plentiful variations in floral coloration and abundant traditional varieties. Here, we used two distinct color-type flowers of C. kanran as experimental materials to elucidate the mechanism of flower coloration. High-performance liquid chromatography (HPLC) analysis revealed that anthocyanins in purple-red-type flowers include three types of anthocyanidin aglycones, peonidin, malvidin, and cyanidin, whereas anthocyanins are lacking in white-type flowers. Through comparative transcriptome sequencing, 102 candidate genes were identified as putative homologues of color-related genes. Based on comprehensive correlation analysis between color-related compounds and gene expression profiles, four candidates from 102 captured genes showed a positive correlation with anthocyanidin biosynthesis. Furthermore, transient expression of CkCHS-1, CkDFR, and CkANS by particle bombardment confirmed that recovery of the expression of them completed the anthocyanin pathway and produced anthocyanin compounds in white-type flowers. Collectively, this study provided a comprehensive transcriptomic dataset for Cymbidium, which significantly facilitate our understanding in the molecular mechanisms of regulating floral pigment accumulation in orchids.